Studies on the number theory of orders - Omar, Mohammed Rafiq (University of Cape Town, 2014)
Bibliography: pages 78-81. === In the nineteenth century no distinction was drawn between maximal and nonmaximal orders in a numberfield. Most of the work on orders in this period was done by Dedekind and Kronecker. The twentieth century has witnessed a relative neglect of the nonmaximal orders of a numberfield, which are the algebraic analogues of singular curves, although a few texts, for example the one by Borevich and Shafarevich, do discuss arbitrary orders. In this dissertation we attempt to present a connected account of the theory of nonmaximal orders, highlighting some of their important properties.